Retroviral analysis reveals the ancient origin of Kihnu native sheep in Estonia: implications for breed conservation - Eve Rannamäe; Urmas Saarma; Anneli Ärmpalu-Idvand; Matthew D. Teasdale; Camilla Speller (NATURE RESEARCH, 2022)
Native animal breeds constitute an invaluable pool of genetic resources in a changing environment. Discovering native breeds and safeguarding their genetic diversity through specific conservation programs is therefore of high importance. Endogenous retroviruses have proved to be a reliable genetic marker for studying the demographic history of sheep (Ovis aries). Previous research has revealed two migratory episodes of domesticated sheep from the Middle East to Europe. The first episode included predominantly 'primitive populations', while the second and most recent is hypothesised to have included sheep with markedly improved wool production. To examine whether the recently discovered Kihnu native sheep in Estonia have historically been part of the first migratory episode and to what extent they have preserved primitive genetic characters, we analysed retroviral insertions in 80 modern Kihnu sheep and 83 ancient sheep from the Bronze Age to Modern Period (850 BCE-1950 CE). We identified that the Kihnu sheep have preserved 'primitive', 'Nordic', and other 'ancient' retrotypes that were present both in archaeological and modern samples, confirming their shared ancestry and suggesting that contemporary Kihnu native sheep originate from the first migratory episode. However, over the course of history, there has been a gradual decrease in the frequency of primitive retrotypes. Furthermore, Kihnu sheep possessed several 'novel' retrotypes that were absent in archaeological individuals, but were shared with improvement breeds, suggesting recent crossing within the last two centuries. To preserve these ancient lineages, our results are being applied in the conservation program of the Kihnu Native Sheep Society.